Sirtuins at the Service of Healthy Longevity - Watroba, Mateusz; Szukiewicz, Dariusz (Frontiers in Physiology, 2021)
Sirtuins may counteract at least six hallmarks of organismal aging: neurodegeneration, chronic but ineffective inflammatory response, metabolic syndrome, DNA damage, genome instability, and cancer incidence. Moreover, caloric restriction is believed to slow down aging by boosting the activity of some sirtuins through activating adenosine monophosphate-activated protein kinase (AMPK), thus raising the level of intracellular nicotinamide adenine dinucleotide (NAD+) by stimulating NAD+ biosynthesis. Sirtuins and their downstream effectors induce intracellular signaling pathways related to a moderate caloric restriction within cells, mitigating reactive oxygen species (ROS) production, cell senescence phenotype (CSP) induction, and apoptosis as forms of the cellular stress response. Instead, it can promote DNA damage repair and survival of cells with normal, completely functional phenotypes. In this review, we discuss mechanisms of sirtuins action toward cell-conserving phenotype associated with intracellular signaling pathways related to moderate caloric restriction, as well as some tissue-specific functions of sirtuins, especially in the central nervous system, heart muscle, skeletal muscles, liver, kidneys, white adipose tissue, hematopoietic system, and immune system. In this context, we discuss the possibility of new therapeutic approaches.